Social Entrepreneurship in Russia as a Topical Communication Activity - A. V. Pryakhina; D. A. Bagdasaryan; A. M. Bukovskaya (Дискурс)
Introduction. The purpose of the article is to analyze the problem of the development of social entrepreneurship in Russia and to determine its role in Russian society. The relevance and scientific novelty of the article are revealed in the review and analysis of a wide range of communication tools used to promote socially oriented enterprises implemented over the past five years in Russia.Methodology and sources. The authors relied on the concepts of the following researchers: S.R. Akhmadieva, Yu.V. Khodkovskaya, A.F. Akhmadieva, N.N. Kiseleva, E.A. Ageeva,  L.S. Pekhova, S.M. Talerchik and others. Also, the authors rely on the Russian civil law. In the study, there were used theoretical methods, such as analysis and synthesis, as well as empirical methods – analysis of documents, network sources of information, content analysis of posts in social networks.Results and discussion. The authors outlined the theoretical and methodological basis for the study of social entrepreneurship, identified the specifics of the development of social entrepreneurship. The study found that the range of tools for promoting social enterprises is wider than that of commercial organizations, however, the main problem remains the lack of, first of all, human resources for large-scale and complex PR activities. Also, the study of social entrepreneurship will reveal and carefully analyze the positive and negative aspects of this innovative business model. This, in turn, will effectively introduce social entrepreneurship into economic and socio-cultural life as a new way to improve the socioeconomic well-being of people. These factors could be considered at the level of both a single region and Russian society as a whole. Thus, the authors should reveal the strategic role of social entrepreneurship in organizing a human-centric Russian society.Conclusion.The relevance of studying social entrepreneurship and its development in society is due to the fact that it is a fairly new activity. Many problems of social entrepreneurship are insufficiently studied, which affects the qualitative argumentation of this phenomenon. Also, the phenomenon of social entrepreneurship has not yet taken root in the minds of many people as an important element in the development of social relations.